"It Ain't He, It Ain't She, It's We": The Politics of Self-Definition and Self-Valuation in The Androgynous Model Web Series. (2nd January 2019) - Blake, Donnesha A.
Abstract : The Androgynous Model web series is a modeling contest whose first season streamed on YouTube between 2013 and 2014. The show features five Black lesbian androgynous models from Charlotte, North Carolina, who compete in a series of photo-shoot and runway challenges to secure the title of "The Androgynous Model." Employing close readings of the photo-shoot, runway challenges, and an interview with the show's creator Nikki Eason, I argue that the models' performances in the web series and Eason's commentary are connected to a Black feminist tradition that prioritizes self-definition and self-valuation. I identify their articulation of self-definition and self-valuation in this web series as BlaQueer Style . Although BlaQueer Style can be and is the styling practices constructed by queer Black people, the interpretive framework BlaQueer Style that I aim to uncover underscores the Black feminist politics embedded in queer Black women's fashion activism so that we can reframe how we define and theorize activism.